Representação da morte feminina em L`Orfeo e Il Combattimento di Tancredi et Clorinda de Claudio Monteverdi - Rocha, Abel Luís Bernardo da [UNESP] (Univ Federal Goias, 2012)
This paper refers to issues related to the harmonic language of Claudio Monteverdi, its harmonic procedures and resulting melodic movements, its use as a dramaturgical resource and its potential allegorical meanings, based on theories and classifications of modes of the sixteenth and seventeenth centuries. At first, it approaches the matter of the multiple names and meanings of the modes and their potential allegorical references according to different authors. Secondly, it presents the analysis of two examples from his operas that deal with the representation of the death of Euridice and Clorinda (Orfeo & Il combattimento de Tancredi e Clorinda, respectively), correlating their harmonic procedures to the corresponding dramaturgical situations.
The Representation of feminine death in L'Orfeo and Il Combattimento di Tancredi et Clorinda by Claudio Monteverdi
Keywords: Harmony in Monteverdi; Opera Conducting; Mode Theory in the 16th and 17th centuries; Music and dramaturgy